Adenoid Cystic Carcinoma of the Esophagus - Chaidir Aulia (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2006)
Adenoid cystic carcinoma is an extremely rare case of the esophagus. We present a female patient, aged 76 years who present with dysphagia and weight loss for the last three month. On endoscopy there was a luminal narrowing in the middle third of the esophagus. Diagnosis was challenging due to the stenosis and the tumor size.   Histopathological   confirmation   was   obtained   by  subcarinal   fine-needle aspiration biopsy. This type of cancer is very aggressive with short survival time. Further studies are needed to define optimal treatment. Keywords: dysphagia, adenoid cystic carcinoma